Estimating the real shock to the economy from COVID-19: The example of electricity use in China - Liu, Lu; Huang, Junbing; Li, Hong (Technological and Economic Development of Economy, 2022)
Quantifying the shock to the economy from the COVID-19 pandemic is difficult. Although this shock is easily linked to financial markets as a sort of monetary shock, few studies have been done on its effect on the real economy. This study takes a particular economic perspective, focusing on electricity uses in various sectors of the economy. We propose a novel method for comparing electricity use in 2019Q1 and 2020Q1, based on which we derive the degree of the real shock to some important economic sectors from COVID-19. In our theoretical framework, demand for energy and its influencing factors are related to the total scale of the economy, i.e., the gross domestic product. Using suitable empirical methods, we obtain certain marginal effects and then calculate the corresponding ratio as the real shock from COVID-19. The ratio between these marginal effects reveals the need for a balance between stocks and the corresponding differences in the economy. In our cases, the electricity use in various economic sectors plays a role in both stocks and the differences. We find that, although manufacturing and consumption are affected, the services are more vulnerable to the shock from the COVID-19 pandemic. Our findings offer implications for policymakers.First published online 09 June 2022